Amelioration of Radiation-Induced Damages in Mice by Curcuminoids: The Role of Bioavailability. (21st April 2021) - Liju, Vijayasteltar B.; Thomas, Angel; Sivadasan, Syam Das; Kuttan, Ramadasan; Maliakel, Balu; IM, Krishnakumar
Abstract: Purpose: The present study investigated the role of free curcuminoids bioavailability on the relative radioprotective efficacy of natural unformulated curcuminoids. Materials and Methods: A food-grade bioavailable formulation of curcuminoids as curcumagalactomannosides (CGM) and unformulated curcuminoids (UC) were employed for the study. Swiss albino mice were randomized into Normal control, Radiation control, Radiation + UC, and Radiation + CGM groups and irradiated with γ-radiation of 6, 8, 10 and 12 Gy. Survival rate, hematological and biochemical parameters, bone marrow cellularity, chromosomal aberrations and histopathology of intestine were followed as a measure of the relative efficacy. Results and Discussion: Oral administration with both UC and CGM at 100 mg/kg. b.wt. produced significant radioprotective effect over the untreated control group of animals. However, CGM treatment was found to provide better clastogenic and genotoxic potential as compared to UC. Further, the histopathology analysis of intestine confirmed the better protective effect of CGM over UC-treated animals. Conclusion: The present study demonstrated the positive role of the bioavailability of curcuminoids in the amelioration of radiation-induced damages in mice since CGM treatment exerted better survival rate and radioprotective effect as compared with UC, despite the relatively low concentrations of curcuminoids in CGM (39% w/w).